PENGABDIAN KEPADA MASYARAKAT MELALUI KULIAH KERJA NYATA (KKN MBKM) DI DESA BULUH RAMPAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Warfa’ni, Warfa’ni; Siti Hikmah Tussa’ada Elsa; Nazwa Aulia Natasya; Afrina Damayanti; najwa shalsa nabilah; dwirianti, dwirianti; ladika anjani; silvy damayanti kamil ginting; rahmad irwanda; sri elvawati (JURNAL PENGABDIAN MANDIRI, 2024)
The MBKM University of Riau Real Work Lecture (KKN) activity in Buluh Rampai Village, Seberida District, Indragiri Hulu Regency is a form of community service. The MBKM KKN program runs from July 15 2024 to August 24 2024. This article describes the various activities carried out by MBKM KKN students in the village. The aim of the MBKM KKN is to provide practical experience and a learning process in exploring village potential that can be developed by the community. Methods for implementing KKN include observation, interviews, and descriptive use of technology. The MBKM KKN student activities are supported by the local government and village community. Some of the activities that have been carried out include: (a) Mutual Cooperation, (b) Private Tutoring, (c) Visits to MSMEs, (d) Visits to local cultural wisdom, (e) Socialization of Clean and Healthy Living Behavior (PHBS), (f ) Creation of Reading Corners, (g) Implementation of educational innovations in schools, (h) Creation of rubbish bins and waste education signs, (i) Holding competitions on August 17, (j) Socialization of anti-bullying, and (k) Planting seeds of Family Medicinal Plants (TOGA)..